Pengaruh Komitmen Profesional, Komitmen Organisasi Dan Intensitas Moral Terhadap Intensi Untuk Melakukan Whistleblowing - Muhammad Esa Seprtian; Muhammad Maulana Hafizh; Nera Marinda Machdar (Journal of Management and Social Sciences, 2024)
This article examines the influence of the variables of professional commitment, organizational commitment and moral intensity on the intention to carry out Whistleblowing. This article was reviewed using relevant previous research as a research source. The results of this article show that: 1). Professional Commitment influences Intention to Whistleblowing, 2). Organizational Commitment influences Intention to Whistleblowing, 3). Moral Intensity influences Intention to Whistleblowing.